Study on high frequency vibration-induced fatigue failure of antenna beam in a metro bogie. (March 2022) - Wu, Xingwen; Xie, Chenxi; Liu, Kaicheng; Wu, Shengchuan; Wen, Zefeng; Mo, Jiliang
Highlights: High frequency vibration of antenna beam has been investigated experimentally. Rail corrugation induced vibration fatigue has been analyzed through the measurements. Coupled vehicle/track dynamic model is formulated considering the flexibility of antenna beam to optimize the structural of antenna beam. A novel design is proposed to enhance the fatigue lifetime of antenna beam. Abstract: This paper investigated on the high frequency vibration-induced fatigue failure of antenna beam through both field tests and numerical simulation. In the field tests, the dynamic stress, acceleration, and operational modal of bogie system as well as the short pitch irregularities of rail were measured to identify the primary contributor to the fatigue failure of antenna beam. The result suggested that the rail corrugation- induced impact with the passing frequency of 78  Hz serves as the main driving force of the modal resonance for bogie frame and antenna beam in the bogie system, which can emphasis the bending of antenna beam and further contribute to the reduced fatigue lifetime. To better understanding the failure mechanism and the associated mitigation method, a rigid/flexible coupled dynamic model of rail vehicle, considering the flexibility of bogie frame, wheelset and antenna beam as well as coil spring, was developed by using the modal synthesis method. Based on the developed model, the influence of elastic rubber mounts located on both ends of antenna beam was investigated, and a new design was proposed to relief the bending movement- induced stress concentration in the antenna beam. This is expected to mitigate the vibration fatigue problem of antenna beam arising from the rail corrugation-induced high frequency wheel/rail impact.